Personal Tourism in Selected EU Countries: A Comparative Analysis - Natalia ZNAMIEROWSKA (Communications of International Proceedings, 2025)
In recent years, intensive changes in tourism have been observed. These changes are driven not only by the consequences of the COVID-19 pandemic but also by evolving societal preferences and improvements in economic conditions. This article presents the results of research on personal tourism in selected European Union (EU) countries. The subject of the study was personal tourism and the changes occurring between 2018 and 2024. The research draws on an analysis of domestic and international literature as well as statistical data from EUROSTAT. The analysis covered selected EU countries. The conducted study revealed that despite the disruptions in the tourism market caused by the COVID-19 pandemic, further development is being observed in the countries under study. The presented analysis serves as an introduction to further research on the trends and changes in personal tourism in EU countries and worldwide.
Keywords: personal tourism; tourism